2012
DOI: 10.1539/joh.11-0100-oa
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Working Hours and Early Childhood Overweight in Japan: A Population‐based Study

Abstract: Toshiharu MITSUHASHI, et al.: Maternal Working Hours and Early Childhood Overweight stratified analysis by the form of maternal employment. Conclusion: Short maternal working hours are associated with a lower odds of early childhood overweight. (J Occup Health 2012; 54: 25-33)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…An ecological study using prefecture-level data reported that the proportion of people completing up to college or university education was inversely associated with the prevalence of childhood obesity. 15 By contrast, other studies using individual-level data reported that maternal educational attainment was not significantly associated with overweight 16 or developmental body mass index (BMI) trajectories 17 among children. These latter studies were not designed to determine the association between SES and adiposity and only included maternal educational attainment as a SES indicator.…”
Section: Introductionmentioning
confidence: 86%
“…An ecological study using prefecture-level data reported that the proportion of people completing up to college or university education was inversely associated with the prevalence of childhood obesity. 15 By contrast, other studies using individual-level data reported that maternal educational attainment was not significantly associated with overweight 16 or developmental body mass index (BMI) trajectories 17 among children. These latter studies were not designed to determine the association between SES and adiposity and only included maternal educational attainment as a SES indicator.…”
Section: Introductionmentioning
confidence: 86%
“…Factors associated with child overweight/obesity included sex of the child, age of the child, mothers’ BMI and work status of the mother as reported in other studies [ 59 61 ]. Maternal overweight/obesity is associated with child overweight/obesity, with high familial risk reported in various studies [ 45 ], [ 60 ].…”
Section: Dissussionmentioning
confidence: 99%
“…Mitsuhashi et al . observed that the prevalence of overweight was 3.12% among children aged 6 years in 1985, and it steadily increased to 4.68% in 2005 …”
mentioning
confidence: 99%
“…2 Mitsuhashi et al observed that the prevalence of overweight was 3.12% among children aged 6 years in 1985, and it steadily increased to 4.68% in 2005. 3 A particular form of kidney disease, so-called obesity-related glomerulopathy (ORG), is characterized by glomerulomegaly with or without focal segmental glomerulosclerosis (FSGS), and the incidence of ORG has increased during the last decade with Correspondence: Yukihiko Kawasaki, MD PhD, Department of Pediatrics, Fukushima Medical University School of Medicine, 1 Hikarigaoka, Fukushima City, Fukushima 960-1295, Japan. Email: kyuki @fmu.ac.jp the increase in obesity, [4][5][6][7] but there have been few reports on pediatric ORG in Japan.…”
mentioning
confidence: 99%